Synthesis and evaluation of N-Mannich bases of isatin-3- (4′-aldehyde/ketone, 2′- thiosemicarbazones) derivatives as potent anticonvulsant agents - Singh S.K.; Jaggi S.; Bharti S.K.; Kulkarni R.G. (My University, 2025)
A series of N-Mannich bases of Isatin-3- (4′- aldehyde/ketone, 2′-thiosemicarbazones) were synthesized with the aim to develop novel anticonvulsant agents. The chemical structure of all the compounds was established by the means of elemental analysis (C, H, N), IR and 1H NMR. The anticonvulsant screening of the compounds was performed using the Maximal Electroshock method and Strychnine induced convulsion method. Compound 11,1- (cyclohexylidenemethylene) - 4 - [(1-(dimethylamino) methyl] - 2-oxo-1, 2-dihydro-3H-indol-1-ylidene) thiosemicarbazone has been found to be a potent anticonvulsant.